Photoshop CC the missing manual® - Snider, Lesa (O'Reilly Media, 2014)
Photoshop CC is an outstanding image editor, but it can be pretty overwhelming. This book makes learning Photoshop as easy as possible by explaining the hows and whys in a friendly, conversational style. Go 3D. Create and edit 3D objects and send them off to a 3D-printing service from inside Photoshop. Export web graphics. Use Generator to instantly export and resize images-just by using layer names.